Design of dual - band 2.4/5.8 GHz antenna using LTCC multilayer technology / Farah Ilina Mazlan - Mazlan, Farah Ilina (2014)
This paper proposed the design of a single - feed Dual - Band 2.4/5.8GHz antenna for WiFi and WiMax application using Low Temperature Co-fired Ceramic (LTCC) multilayer technology. The used of LTCC in this project is for the purposed of providing a compact microstrip-like antenna with high gain and good performance. The design consists of 8 LTCC layers with a single silver patch mounted which resonates the lower frequency of 2.4GHz and upper frequency of 5.8GHz with the bandwidth of 47.3MHz and 56.8MHz respectively. The gain for lower band is -0.7dB and l.6dB for the upper band. By modifying the rectangular patch with inserted slits and a single feed line attach, the proposed antenna had meet its purposed in this design which is to achieve the target frequencies 2.4/5.8GHz. The antenna comprises a total dimension of 35 x 30 x 0.788 mm3.